2007
DOI: 10.2527/jas.2006-738
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of mathematical functions to describe growth and efficiency of phosphorus utilization in growing pigs1

Abstract: Success of pig production depends on maximizing return over feed costs and addressing potential nutrient pollution to the environment. Mathematical modeling has been used to describe many important aspects of inputs and outputs of pork production. This study was undertaken to compare 4 mathematical functions for the best fit in terms of describing specific data sets on pig growth and, in a separate experiment, to compare these 4 functions for describing of P utilization for growth. Two data sets with growth da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 17 publications
3
25
0
Order By: Relevance
“…Similar to poultry growth, Kebreab et al (2007) reported for pigs that using a more complex (four parameter) function resulted in lower BIC values (therefore, better) than using three parameter functions and the additional parameter was justified because it gave flexibility to a growth function. The authors argue that although the Gompertz has been used extensively, four parameter growth functions such as the Richards were superior in describing growth over time and are recommended for use in growth data analysis in monogastric animals.…”
Section: Comparing Growth Functionsmentioning
confidence: 94%
“…Similar to poultry growth, Kebreab et al (2007) reported for pigs that using a more complex (four parameter) function resulted in lower BIC values (therefore, better) than using three parameter functions and the additional parameter was justified because it gave flexibility to a growth function. The authors argue that although the Gompertz has been used extensively, four parameter growth functions such as the Richards were superior in describing growth over time and are recommended for use in growth data analysis in monogastric animals.…”
Section: Comparing Growth Functionsmentioning
confidence: 94%
“…Population based methods (mixed models) have been more widely applied in analysis of pig growth (Criag and Schinckel, 2001;Kebreab et al, 2007). It is assumed that all animals follow the same functional form with parameters varying according to multivariate normal distribution.…”
Section: Resultsmentioning
confidence: 99%
“…The bilinear relationship between NI and FN was explained by Kebreab et al (7) that microbial FN increased with increasing available energy for the growth of microbial cells, but as the amount of microbial synthesis approached optimum according to the available energy, the contribution to MFN remained constant so the increase in FN was mostly as indigestible N from the protein consumed. In support of the monomolecular model that predicts N excretion better, Kebreab et al (35) noted that the monomolecular equation was best at determining efficiencies of phosphorus utilisation for body weight gain compared with the sigmoidal model. Schulin-Zeuthen et al (23) also showed that the monomolecular model was the best predictor of the relationship between phosphorus retention and available phosphorus intake compared with linear and Gompertz models.…”
Section: Discussionmentioning
confidence: 99%
“…The sigmoidal curve follows through four phases i.e. lag phase, accelerating phase, deceleration phase and stationary phase (35) . This suggests that NR pattern v. NI may remain lag phase at low NI until basal N requirement is fulfilled, followed by accelerating NR starting from the end of lag phase, then NR goes into the decelerating phase and finally NR does not improve with increasing NI when the optimum live weight gain of animals is reached.…”
Section: Discussionmentioning
confidence: 99%